Improving Students’ Vocabulary Mastery by Using Fly Swatter Game - Pilongo, Jolanda Hulda Debora; Mohammad, Titien Fatmawaty; Bonde, Citra Dewi (Research Review: Jurnal Ilmiah Multidisiplin, 2022)
This research analyzes effect of fly swatter game in improving students’ vocabulary mastery. A quantitative method is employed in discovering the results, where it is conducted at SMP N 5 Dumogaand the participants were the A class of eight-grade students of SMP N 5 Dumoga. Data collection was employed by using pre- and post-test and the treatment is used as a means of improving students’ vocabulary mastery. The results showed that there is an improvement in students’ vocabulary mastery, which can be seen from the higher post-test score. Furthermore, by implementing fly swatter game, the students are being more active and enthusiasm in learning vocabularies related to the material taught by the researcher. As a result, they are not feel bored and keep their interest in following the learning process.Therefore, based on the explanation above, it can be summarized that the students’ vocabulary mastery is improved because of the implementation of Fly Swatter Game in teaching and learning process.